Near-Minimum Time Visual Servo Control Of An Underactuated Robotic Arm - Benbelkacem, Yacine (2013)
In industrial robotics, grasping an object is required to happen fast since the position and orientation of such an object is a-priori known. However, if such information about the position and orientation is unavailable and objects are spread randomly on a conveyor, it may be challenging to keep the dexterity and speed at which the task is carried out. Nowadays, the use of vision sensors to compute the position and orientation of an object and to reposition the robotic system is being used accordingly. This technology has indirectly introduced a disparity in time that varies according to the nature of the control technique.